Housing, Health and Happiness - Matias Cattaneo; Sebastian Galiani; Paul Gertler; Sebastian Martinez; Rocio Titiunik (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2008)
Despite the importance of housing for people's well-being, there is little evidence on the causal impact of housing and housing improvement programs on health and welfare. In this paper, we help to fill this gap by investigating the impact of a large-scale effort by the Mexican Government to replace dirt floors with cement floors on child health and adult happiness. We find that replacing dirt floors with cement floors significantly improves the health of young children. Specifically, we find significant decreases in the incidence of parasitic infestations, diarrhea, and the prevalence of anemia, and an improvement in children's cognitive development. Additionally, we find that replacing dirt floors by cement floors significantly improves adult welfare, as measured by increased satisfaction with their housing and quality of life, as well as by lower scores on depression and perceived stress scales.
Keywords: I12; I38; H43; 330; Wohnung; Soziale Wohnungspolitik; Gesundheit; Zufriedenheit; Mexiko